2021
DOI: 10.3390/antibiotics10060746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microalgae Antiviral Activity and Their Bioactive Compounds

Abstract: During the last year, science has been focusing on the research of antivirally active compounds overall after the SARS-CoV-2 pandemic, which caused a great amount of deaths and the downfall of the economy in 2020. Photosynthetic organisms such as microalgae are known to be a reservoir of bioactive secondary metabolites; this feature, coupled with the possibility of achieving very high biomass levels without excessive energetic expenses, make microalgae worthy of attention in the search for new molecules with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 162 publications
(250 reference statements)
0
30
0
Order By: Relevance
“…Bioactive compounds in microalgae have been shown to provide an innovative role to enhance antimicrobial, antiviral and antiparasitic activities (Chen et al, 2016;Carbone et al, 2021;Yi et al, 2021;Sonkamble and Wagh, 2022). Ghania et al (2019) confirmed the antimicrobial and antiparasitic activities of three Algerian algae from the northwest coast.…”
Section: Activitiesmentioning
confidence: 73%
“…Bioactive compounds in microalgae have been shown to provide an innovative role to enhance antimicrobial, antiviral and antiparasitic activities (Chen et al, 2016;Carbone et al, 2021;Yi et al, 2021;Sonkamble and Wagh, 2022). Ghania et al (2019) confirmed the antimicrobial and antiparasitic activities of three Algerian algae from the northwest coast.…”
Section: Activitiesmentioning
confidence: 73%
“…Another indicator of the pyrimidine metabolism pathway found in the NMR spectra aside from glutamine was the presence of hypoxanthine. This metabolite is important due to its role in microalgae metabolism as a precursor of xanthine, which can be used to synthesize bioactive substances, such as astaxanthin [ 48 ], theobromine, and other methylxanthines, which have been reported to be antiviral agents against numerous pathogens, including SARS-CoV-2 [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, microalgal lipids may serve as a source for biofuels, building blocks in the chemical industry, and value-added edible oils for the functional food and health market [9,10]. Moreover, microalgal proteins, carbohydrates, and pigments may find application in the food, feed, health, and bulk chemical market, or for the production of ethanol and chemicals [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%